Mesenchymal tumours of the gastrointestinal tract - Sbaraglia, Marta; Businello, Gianluca; Bellan, Elena; Fassan, Matteo; Dei Tos, Angelo Paolo (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2021)
Mesenchymal tumours represent a heterogenous group of neoplasms encopassing benign, intermediate malignancy, and malignant entities. Sarcomas account for approximately 1% of human malignancies. In consideration of their rarity as well as of intrinsic complexity, diagnostic accuracy represents a major challenge. Traditionally, mesenchymal tumours are regarded as lesions the occurrence of which is mostly limited to somatic soft tissues. However, the occurrence of soft tissue tumours at visceral sites represent a well recognized event, and the GI-tract ranks among the most frequently involved visceral location. There exist entities such as gastrointestinal stromal tumours (GIST) and malignant gastointestinal neuroectodermal tumors that exhibit exquisite tropism for the GI-tract. This review will focus also on other relevant clinico-pathologic entities in which occurrence at visceral location is not at all negligible.